2019
DOI: 10.1002/app.48523
|View full text |Cite
|
Sign up to set email alerts
|

Starch‐based biodegradable hydrogel as seed coating for corn to improve early growth under water shortage

Abstract: In this work, the effect of a biodegradable hydrogel as a seed coating on the early growth of corn seed was studied. The hydrogel was a succinate‐modified potato starch, and it had an equilibrium water absorption capacity of 260 g distilled water (DW)/g hydrogel. To coat corn seeds, the seeds were slightly wetted with an aqueous adhesive solution and then, in a closed container, mixed with a dry mixture of the modified starch (MS), bentonite, and talc. The damp coated seeds were air‐dried at 40 °C for 24 h. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…MI/g•10 min (190 °C, 2.16 kg) 2.1 1.9 1.5 1.1 0.9 Density/g•cm 3 1.227 1.266 1.224 1.228 1.226 Figure 9 was the TGA spectrum for the TPS/PBSA/PLA composites in N2. As dis played in the TGA spectrum, there were four steps in the spectrum of the TPS/PBSA/PLA composites, and steps in the spectrum meant the degradation of composites.…”
Section: Properties Of the Tps/pbsa/pla Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…MI/g•10 min (190 °C, 2.16 kg) 2.1 1.9 1.5 1.1 0.9 Density/g•cm 3 1.227 1.266 1.224 1.228 1.226 Figure 9 was the TGA spectrum for the TPS/PBSA/PLA composites in N2. As dis played in the TGA spectrum, there were four steps in the spectrum of the TPS/PBSA/PLA composites, and steps in the spectrum meant the degradation of composites.…”
Section: Properties Of the Tps/pbsa/pla Compositesmentioning
confidence: 99%
“…Starch, the second largest natural polymer on earth, is widely synthesized by plants. Due to the renewable, biodegradable resource and low price, starch is widely used in the manufacturing industry for food, medicine, plastic and chemical packaging [1][2][3][4][5][6]. At present, the production of starch degradable plastics accounts for more than 60% of the total production of degradable plastics [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Oksińska et al [ 47 ] identified two bacteria, Rhizobium radiobacter 28SG and Bacillus aryabhattai 31SG, isolated from the watered SAP, that were able to biodegrade up to 36% of the similar copolymer of acrylamide and potassium acrylate containing 5.28% of unpolymerized monomers in 30 days. Despite the expected biodegradability, there are efforts to replace synthetic SAPs with natural ones such as starch [ 21 ], cellulose [ 14 ], chitosan or alginate [ 22 ], or with synthetic-biopolymer hybrid SAPs that combine the desired chemical properties of synthetic polymers–such as mechanical strength, high water capacity, and stability, and lower cost and biological safety of natural polymers [ 48 ]. Proteins are also currently gaining a lot of attention as a replacement for synthetic SAPs because they are biodegradable and available from agricultural waste [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this technology enables to minimize the amount of applied SAP compared to the addition as a soil supplement. In seed coating technology, synthetic polymers are commonly used [ 18 , 19 ] due to their suitable chemical properties, but natural polymers such as hydroxypropyl methylcellulose [ 20 ], starch [ 21 ], or chitosan with alginate [ 22 ] have also been tested. The application of SAPs as swelling hydrogels on the seed surface creates a direct line of available water for seeds and can help plants cope with water shortage during the germination and early growth phase.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to reduce the fossil fuel–based polymers and owing to the biodegradable nature, ease of availability, and generally low cost of the precursors, biodegradable polymers have been used in seed coating over the last two decades. Gelatin [ 25 ], gums [ 25 , 28 ], CS [ 24 , 29 ], cellulose and its derivatives [ 23 , 29 , 30 ], starch [ 26 , 31 ], and alginates [ 32 ] are some of the biopolymers that are used alone or in combination with other materials as seed coats for targeted delivery of AIs and enhanced growth and preservation of plants. However, most of the biopolymers have to be used with additional substances, that is, surfactants and film formers.…”
Section: Biodegradable Seed Coatingsmentioning
confidence: 99%